Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1176/appi.ajp.2015.15091188
|View full text |Cite|
|
Sign up to set email alerts
|

Perinatal Phosphatidylcholine Supplementation and Early Childhood Behavior Problems: Evidence for CHRNA7 Moderation

Abstract: Objective α7-Nicotinic receptors are involved in the final maturation of GABA inhibitory synapses before birth. Choline at levels found in the amniotic fluid is an agonist at α7-nicotinic receptors. The authors conducted a double-blind placebo-controlled trial to assess whether high-dose oral phosphatidylcholine supplementation during pregnancy to increase maternal amniotic fluid choline levels would enhance fetal development of cerebral inhibition and, as a result, decrease childhood behavior problems associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
69
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 108 publications
(72 citation statements)
references
References 39 publications
(54 reference statements)
1
69
0
Order By: Relevance
“…Recent studies suggest that dietary phosphatidylcholine supplementation during the second and third trimesters may prevent cerebral inhibition deficits associated with schizophrenia and attention deficit disorder. 53 There is also evidence suggesting that vitamin D supplementation during pregnancy may reduce rates of low birthweight and preterm delivery, 54 which have been associated with attention deficits and increased risk for childhood behavioural and emotional disorders. 55,56 .…”
Section: Universal Preventive Interventionsmentioning
confidence: 99%
“…Recent studies suggest that dietary phosphatidylcholine supplementation during the second and third trimesters may prevent cerebral inhibition deficits associated with schizophrenia and attention deficit disorder. 53 There is also evidence suggesting that vitamin D supplementation during pregnancy may reduce rates of low birthweight and preterm delivery, 54 which have been associated with attention deficits and increased risk for childhood behavioural and emotional disorders. 55,56 .…”
Section: Universal Preventive Interventionsmentioning
confidence: 99%
“…During gestation, maternal choline deficiency reduces global DNA methylation in the fetal hippocampus and alters the development and function of cholinergic neurons that participate in learning, memory, and attention (Mellott et al, 2007; Zeisel, 2007). A recent study showed that perinatal phosphatidylcholine supplementation (above current standards) is associated with less social withdrawal and fewer attention-deficit problems in ~3 year-old children compared to an age-matched placebo group (Ross et al, 2016). Remarkably, it is estimated that 90–95% of pregnant women fail to meet the minimum recommended levels of choline intake (Brunst et al, 2014).…”
mentioning
confidence: 99%
“…Further investigation of aging and MCS treatment shows an increase in ChAT intensity in 2N animals, but not in Ts65Dn mice when examined pre-BFCN degeneration (4-6 MO) and post-BFCN degeneration (14-18 MO), however this may be explained by the fact that unsupplemented Ts65Dn mice display septohippocampal degeneration during the aging process . MCS has also been shown to protect the cholinergic system in a mouse model of amyloid-beta precursor protein (APP) overexpression (Mellott et al, 2017) and behavioral and morphologic benefits in several models of neurodevelopmental disorders (Bearer, Wellmann, Tang, He, & Mooney, 2015;Ross et al, 2016;Scremin, Roch, Norman, Djazayeri, & Liu, 2015;Stevens et al, 2008;Ward, Agarwal, Wang, Berger-Sweeney, & Kolodny, 2008;Kolodny, Nag, & Berger-Sweeney, 2009), indicating that the effects are broadly neuroprotective across several disease entities.…”
mentioning
confidence: 99%